PENGARUH SUPERVISI AKADEMIK DAN MOTIVASI BERPRESTASI TERHADAP KINERJA GURU SMP NEGERI DI KOTA PONTIANAK - Mahmudah, Himmah; Asrori, Muhammad; Chiar, Muhammad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to reveal the effect of academic supervision and achievement motivation toward the performance of Junior high school teachers in Pontianak. This research applied qualitative method of analitic description Teachers of stated junior high school teachers which have been teaching more than three years were the population of this research. The total number of the population were 954. Using the table Bartlett, Kotrlik dan Higgins, the reseacher determined 106 teachers as the sample of this research. In order to analyze the data, the researcher used aplication of SPSS 20. The hypothesis were tested using double regretion analysis. The result show that: (1) based on the scale used in this research,academic supervision conducted by the school principal toward their teachers is categorized good (2) achievement motivation of state junior high school teachers was categorized good (3) the performance of state junior high school teachers is very good (4) it is found that there is a positive correlation between academic supervision conducted by school principal toward state junior school teachers performance in Kota Pontianak with the score 24,7%, (5) positive and significant correlation was also foundÂ between the achievement motivation and and the teachers performance with score 65%, (6) positive and signicifant correlation between academic supervision and achievement motivation toward state junior high school in Pontianak, with the score 53,2%.Â Keywords: Academic supervision, achievement motivation, teachersâ€™ performance